Concept Mapping and Knowledge Modeling: A Multi-Disciplinary Educational, Informational, and Communication Technology - John W. Coffey (Journal of Systemics, Cybernetics and Informatics, 2020)

(untitled)
Concept maps are useful in many disciplines for the representation and communication of structured knowledge. This article contains a description of concept mapping and knowledge modeling based upon concept maps that are used for a variety of purposes. It describes applications of concept mapping and knowledge modeling for education, for knowledge preservation and sharing, for knowledge creation, as an efficient means of creating documentation, and for the creation of knowledge formalisms from informal knowledge representations. Examples are drawn from several different knowledge domains.